The Fabrication of Qualified Citizens: from the “Expert-Hand Worker” to the “Scientific Minded” - Andrade-Molina, Melissa (Perspectivas da Educação Matemática, 2017)
Within the practices of school mathematics there exists many naturalized truths that have been (re)produced in different times and in different places. The belief of mathematics education becoming the key to economical progress assuring the future growth of nations is problematized. By following a rhizomatic analytical move, a historization of the present is deployed to map the fabrication of the desired qualified citizen in Chile. The analysis evidences the (re)production of dominant narratives about the “qualified citizen” are and have been entangled with the functioning of school geometry and school mathematics, as a technology of government of the self to fabricate the Modern rational subject by inserting students in particular forms of being and knowing in the world.